Identification and correction of inefficiencies during elite competitive swimming - Mason, B.; Mackintosh, C. (ISBS Proceedings Archive (Michigan), 2020)
Olympic Games and World Championship swimming events are often not won by the fastest swimmer. In many events the free swimming speed of many of the competitors is almost identical, however it is the better starter in sprint events and the better turner in distance events who is victorious. The authors of this paper worked for over twenty years with analysis systems for starts and turns in elite swimming at the Australian Institute of Sport and over the last six years have developed, with the Kistler company, a commercial swim start and turn analysis system to assess elite swimmers. This paper will discuss inefficiencies in the starts and turns that were found to be commonly identified in elite swimmers and then state how these inefficiencies in performance may be rectified.